Evaluation of incidence of cryptorchidism with special reference to anatomical and clinical aspects - Suresh, N. M.; Katttepura, Subramanya; Afroze, Khizer Hussain; P., Ramesh; Bhaskar, Apurva (International Journal of Contemporary Pediatrics, 2018)
Background: Cryptorchidism is simply defined as the absence of one or both testes from the scrotum. It is the most common birth defect of the male genitalia. The testis may be located intra-abdominal or inguinal. This article mainly deals with embryology, etiology, anatomy and incidence types of cryptorchidism in Tumakuru rural district. Methods: This study was interdepartmental and prospective, consisting of 66 cases conducted at the Department of Pediatric Surgery and Anatomy and the period of study was from April 2013- March 2017. Cryptorchidism has been classified into 1) Intra-abdominal, 2) Inguinal, 3) Ectopic testis (perineum). Results: Out of 66 cases, testis in inguinal canal is the most common incidence followed by the intra-abdominal and Ectopic testis. Least found was ectopic and torsion in the inguinal canal. Complications are torsion and vanishing testis. Conclusions: This condition is repairable in a vast majority of cases. Early diagnosis and surgical intervention have to be carried out to correct this defect.